Healthcare access barriers by mental health status among South Asian adults in Hong Kong: an exploratory cross-sectional study - Zhaoyi Zhu; Gary Ka-Ki Chung; Danna Camille Vargas; Bulbul Sharma; Kai Sing Sun; Heidi Hung; Tsz Lui Tang; Man Hin Chio; Hasiba Munir; Mariem Sharif; Chi Yui Wong; Winne Kought; et al. (BMC Public Health, 2026)
Abstract Background Access to healthcare services has a considerable impact on overall health at all stages of life. Depression and anxiety, coupled with migrant or ethnic minority status, may amplify unique challenges in accessing healthcare, including social, economic and language barriers. This study investigates the relationship between mental health and healthcare access barriers among South Asian adults in Hong Kong. Method A cross-sectional survey with 604 South Asian adults residing in Hong Kong was conducted from November 2023 to March 2025. Depression and anxiety were assessed with the 4-item Patient Health Questionnaire, whereas access barriers were measured with ten items adapted from the US National Health Interview Survey. Multiple regression analyses were employed with progressive adjustments for demographic, socioeconomic, health-related, and psychosocial factors. Results Almost all participants reported at least one barrier to healthcare access (99.3%), with no usual source of care (NUSC) being identified as the most commonly reported barrier (90.1%). In the multivariable regression models, depression/anxiety symptoms were not significantly associated with NUSC (OR = 1.60 [95% CI: 0.83, 3.08]), while they were robustly linked to more availability-related barriers (RR = 1.45 [1.15, 1.84]), and affordability concerns (OR = 1.63 [1.08, 2.48]) after full adjustment. Conclusion These findings suggest that mental health conditions restrict healthcare access in terms of availability and affordability among South Asians in Hong Kong. Culturally appropriate interventions are warranted to address both psychological and social determinants underlying these specific access dimensions to mitigate the healthcare disparities.